Operant Conditioning Pembelajaran Kitab U’yunul Masail Lil Nisaa Santri Kelas 3 Tsanawiyah Madrasah Hidayatul Mubtadiin Lirboyo Kediri - Santoso Santoso; Intan Wulandhari; Abbas Sofwan Matlail Fajar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The development of education needs to be observed so that the purpose of education can be achieved. So there needs to be an accurate learning theory base, so that learning can be in line with the expected purpose. This research aims to find out operant conditioning book learning U'yunul masail lil nisaa 3rd grade students of Tsanawiyah Madrasah Hidayatul Mubtadiin Lirboyo Kediri. The type of research used is qualitative with a descriptive approach. The discussion in this article is about the basic concepts of B.F Skinner's theory operant conditioning; schedule of reinforment , shaping , behaviors modification , generalization discrimination. The results of this research produce learning U’yun masail lil nisaa It starts with the teacher reading the material then explaining it on the blackboard and the teacher asking questions to the students for those who don't understand, then the teacher repeats the explanation again. Second, the formation of learning starts from providing material reinforcement starting from menstruation, postpartum, istihadhoh And thoharoh which is implemented in stages. Third, before starting learning, students discuss first to repeat the lessons they have learned. Fourth, the teacher provides different information about the material, then the students come forward to answer the known information. If they are unable, another friend comes forward to explain the known material.